Storage Management in Data Centers: Understanding, Exploiting, Tuning, and TroubleshootingVeritas Storage Foundation - Scriba, Albrecht; Herminghaus, Volker (SpringerLink Bücher, 2009)
Storage Management in Data Centers helps administrators tackle the complexity of data center mass storage. It shows how to exploit the potential of Veritas Storage Foundation by conveying information about the design concepts of the software as well as its architectural background. Rather than merely showing how to use Storage Foundation, it explains why to use it in a particular way, along with what goes on inside. Chapters are split into three sections: An introductory part for the novice user, a full-featured part for the experienced, and a technical deep dive for the seasoned expert. An extensive troubleshooting section shows how to fix problems with volumes, plexes, disks and disk groups. A snapshot chapter gives detailed instructions on how to use the most advanced point-in-time copies. A tuning chapter will help you speed up and benchmark your volumes. And a special chapter on split data centers discusses latency issues as well as remote mirroring mechanisms and cross-site volume maintenance. All topics are covered with the technical know how gathered from an aggregate thirty years of experience in consulting and training in data centers all over the world.